A therapeutic vascular conduit to support in vivo cell-secreted therapy - Edward X. Han (Nature Portfolio, 2021)
Abstract A significant barrier to implementation of cell-based therapies is providing adequate vascularization to provide oxygen and nutrients. Here we describe an approach for cell transplantation termed the Therapeutic Vascular Conduit (TVC), which uses an acellular vessel as a scaffold for a hydrogel sheath containing cells designed to secrete a therapeutic protein. The TVC can be directly anastomosed as a vascular graft. Modeling supports the concept that the TVC allows oxygenated blood to flow in close proximity to the transplanted cells to prevent hypoxia. As a proof-of-principle study, we used erythropoietin (EPO) as a model therapeutic protein. If implanted as an arteriovenous vascular graft, such a construct could serve a dual role as an EPO delivery platform and hemodialysis access for patients with end-stage renal disease. When implanted into nude rats, TVCs containing EPO-secreting fibroblasts were able to increase serum EPO and hemoglobin levels for up to 4 weeks. However, constitutive EPO expression resulted in macrophage infiltration and luminal obstruction of the TVC, thus limiting longer-term efficacy. Follow-up in vitro studies support the hypothesis that EPO also functions to recruit macrophages. The TVC is a promising approach to cell-based therapeutic delivery that has the potential to overcome the oxygenation barrier to large-scale cellular implantation and could thus be used for a myriad of clinical disorders. However, a complete understanding of the biological effects of the selected therapeutic is absolutely essential.